Breastfeeding and wheeze prevalence in pre‐schoolers and pre‐adolescents: the Genesis and Healthy Growth studies. Issue 8 (2nd December 2013) - Guibas, George V.; Xepapadaki, Paraskevi; Moschonis, George; Douladiris, Nikolaos; Filippou, Amalia; Tsirigoti, Lydia; Manios, Yannis; Papadopoulos, Nikolaos G.
Abstract Background To date, extensive research has been undertaken on a potential link of breastfeeding (BF) to wheezing illnesses. Nevertheless, an association remains to be established, partly due to age‐dependent discrepancies and different definitions of exposures/outcomes across studies. We thus investigated the relation of diverse infantile feeding patterns with wheeze/asthma prevalence in two cohorts of children of different ages (preschool and preadolescent). Methods Wheeze ever/in the last 12 months (current) and doctor‐diagnosed asthma were retrospectively reported by parents of the participants of two cross‐sectional studies: the Genesis study (1871 children aged 1–5) and the Healthy Growth study (1884 children aged 9–13). Information on feeding practices (exclusive breastfeeding vs. mixed vs. formula feeding) and their duration (2 vs. 4 vs. 6 months) was recorded. Perinatal and anthorpometric data were also collected. Results In pre‐schoolers, regimes that did not entail exclusive BF were positively correlated to current/ever wheeze, both before and after adjustment for confounders. No differences between the associations of regimes with 2, 4 or 6 months of exclusive BF with current/ever wheeze were shown. Furthermore, there was no consistent correlation of feeding practices with physician‐diagnosed asthma. In pre‐adolescents, no association of infantile feeding patterns with the wheeze/asthma outcomes was observed. Conclusions Exclusive BF is associated with reduced prevalence of current/ever wheeze in pre‐schoolers; however, this appears to wane in older children. The association of a period of exclusive BF as low as 2 months with pre‐school wheeze prevalence, appeared to be comparable with that of 6 months of exclusivity.